Some anatomical notes on the silk glands of Hydrophiloidea (Coleoptera Hydraenidae, Helophoridae, Hydrophilidae, Sphaeridiidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Out of 14 examined species, the widest equipment of silk glands was found in Hydrophilus caraboides (Hydrophilidae ), which bears two groups of tubular units, each referred here as apical gland and basal gland. The latter is present in most Hydrophilidae and in all Sphaeridiidae and exhibits a very wide interspecific variability in its shape. On the contrary, the apical gland was found only in another species, Helophorus maritimus grandis (Helophoridae). In Helochares lividus (Hydrophilidae), which apparently lacks glands, silk is ascertainly produced by calices. Apparent absence of silk gland was detected also in the cocoon-producer Helophorus minutus (Helophoridae) and Ochthebius exaratus (Hydraenidae). Although recent papers state a mesoderruic origin for silk glands of Hydrophiloidea, principles of Entomology suggest an ectodermic origin for a part of them at least.
Keywords: presence/absence; interspecific variability